Metabolite Profile of Crescentia cujete L. Fruit Infusion Based on LC-MS Analysis and Its Toxicity Against Artemia salina Leach: Profil Metabolit Infusa Buah Majapahit (Crescentia cujete L.) Berdasarkan Analisis LC-MS serta Uji Toksisitas terhadap Artemia salina Leach - Rahma Martha; Danar Danar (Ma Chung Press, 2026)
Cancer is a disease characterized by uncontrolled cell proliferation due to cell cycle dysregulation. The development of natural product-based anticancer compounds offers a safer and more effective therapeutic alternative. This study aimed to identify the secondary metabolites in the fruit pulp infusion of Crescentia cujete L. (calabash) using Liquid Chromatography–Mass Spectrometry (LC-MS/MS) and to evaluate its cytotoxic potential via the Brine Shrimp Lethality Test (BSLT). This experimental study utilized Crescentia cujete fruit pulp infusion prepared by the aqueous infusion method. The LC-MS/MS analysis successfully identified 101 metabolites, predominantly flavonoids, specifically kaempferol-3-O-rhamnoside (3.29479%) and hesperidin (3.18572%). The cytotoxicity test against Artemia salina Leach larvae revealed an LC50 value of 675.46 ppm, indicating that the infusion is classified as toxic (LC50 < 1000 ppm) and possesses potential as an anticancer candidate for preliminary screening. These findings suggest that Crescentia cujete fruit pulp infusion is a promising source of secondary metabolites for the development of natural product-based anticancer drugs. Future studies are required to confirm this cytotoxic activity through in vitro assays on cancer cell lines and in vivo models to establish its efficacy and safety.